Incidence of complications following non-watertight dural reconstruction with a non-suturable, absorbable collagen matrix onlay graft in elective cranial surgery - Ali, Asman; Saha, Debadatta (International Surgery Journal, 2020)
Background: Collagen matrices are effective duraplasty grafts with increasing acceptability. However, little evidences exits for dural reconstruction utilizing monolayer collagen matrix onlay graft in a non-watertight fashion. Purpose of our retrospective analysis was to advance our understanding of the use of semisynthetic collagen as dural substitute in elective cranial surgery. Methods: A consecutive series of sixty patients who underwent elective cranial surgery, where non-watertight dural reconstructions were done with a non-suturable, absorbable collagen matrix onlay graft, has been analysed retrospectively. Results: Overall, the most common indication for duraplasty was tumor resection (93.3%). CSF leak rate was 10.0%. Incidence of aseptic meningitis was 8.3% and all cases has been resolved with steroids alone. Similarly, postoperative surgical site infection rate was 8.3%. Incidence of pseudomeningocele in follow-up was 6.7%. Only in one case (1.7%), permanent CSF (cerebrospinal fluid) diversion was needed due to troublesome CSF leak with associated hydrocephalus. Conclusions: Semisynthetic, monolayer collagen matrix used as an onlay dural graft is a simple, yet an attractive alternative in duraplasty due to their easy handling, lower surgical time, and high biocompatibility, where primary dural closure is undesirable or not feasible. Our study provides greater insight into non-water tight duraplasty procedure. However, further study is needed to determine the optimal strategy for dural reconstruction. Data from this study may be used to compare alternative methods of dural reconstruction in elective cranial surgery.